The influences of Islamic marketing strategy towards potential motor takaful customer / Nur Akmal Diyana Mohamad Nazri - Mohamad Nazri, Nur Akmal Diyana (2016)
Motor takaful is a type of Islamic banking product that pools the fund from the depositors based on Tabarruq contract to protect a vehicles of the customers. In conventional system, also has this types of services called motor insurance. The demands of this two products have their own main and specific factors that influence their customer preferences. In Malaysia, majority the owner of vehicle using motor insurance compare to motor takaful. In order to increase the customer or subscriber of the motor takaful, the good plan of Islamic marketing strategy is really important and crucial to be focus on. Thus, this paper will show what the factors of Islamic marketing strategy that influence the potential motor takaful customer. This will help to strengthen the takaful company in Malaysia that promote Islamic banking products which based on Shariah principle. Objective: The main objective of this study is to identify the main factor of the Islamic marketing sfrategy that influences the potential motor takaful customer. Specific objectives for this study are as follows. Firstly, to identify the relationship between Islamic branding and the potential motor takaful customer. Secondly, to identify the relationship between Islamic pricing and the potential motor takaful customer. Thirdly, to identify the relationship between Islamic networking and the potential motor takaful customer. Dependent variable is the potential motor takaful customer. Independent variables is Islamic Branding, Islamic Pricing and Islamic Networking. Sample description is in data description, the survey that will be used in this research is a causal-type of the survey, whereby 100 questionnaires are going to be distributed to the potential motor takaful customer in Kuala Lumpur, Selangor and Johor area. Questions that arise are based on the variables that will form the result of this research. Econometric method/statistical method in this study is by using SPSS statistical software by using Pearson Correlation on order to investigate the relationship between dependent variable and independent variables. Besides that, using multiple regression to achieve the objectives.